Integración de Repositorios Digitales para la Gestión del Conocimiento en el ámbito universitario Colombiano - Cano Olivera, Luis Eduardo; Espitia Zambrano, Pedro Enrique; Perez Castillo, Jose Nelson; Jayanes Aguilar, Luis (Ingeniería, 2008)
This article presents the steps to realize the changes of integration and migration of information of digital repositories in different platforms of Open Source (Open Source) in order to guarantee the standardization of any proper informatic solutions of the Universities of High School (UHS). In addition to improving the access to the application preventing persons not authorized to the UHS from registering inside the system. Addition to this problem, it exists the one that hasappearing inside the Information Technologies and the Communications (ITCs), with the heyday of information that is registered second to second on a global scale by the phenomenon of the Web 2.0 [9]. Information that in most cases cannot be re-used so much by research centers and/or academic sector after there did not exist suitable informatic tools that allow to centralize the knowledge management in a certain place and of way specialized according to the different Basic Nuclei of the Knowledge (BNK) that exist inside the educational sector [5], without forgetting also the costs in the licenses of software that could exist. Although the movements of the free software [6] 7] and with the open source [8], which must not make a mistake, they have provided some informatic tools for the knowledge management; in most cases this tools cannot integrate between themselves with other information systems who has an UHS, due to few documentation that exists and/or to the only specification started to a certain computer language and/or engine of database and/or technological platform with which they were developed, between others. Forcing that in a certain UHS has to realize different implementations decentralized with redundant information in his information systems, without these being synchronized with other informatic solutions that the same institution has.